Enhancing the thermal stability of the bulk-heterojunction photovoltaics based on P3HT/PCBM by incorporating diblock amphipathic P3HT–PEO at D/A interface. Issue 66 (29th June 2016) - Liu, Jikang; Zhu, Xiaoguang; Li, Junli; Shen, Jiulin; Tu, Guoli
Abstract : A diblock amphipathic copolymer P3HT–PEO was rationally designed and easily synthesized. Abstract : A diblock amphipathic copolymer P3HT–PEO was rationally designed and easily synthesized. By introducing P3HT–PEO into P3HT/PCBM blends, the intramolecular interaction between the P3HT–PEO and the donor/acceptor (D/A) molecule in the blends could make the P3HT–PEO located at P3HT/PCBM domains' interface, which could stabilize the morphology of the bulk-heterojunction and also suppress the acceptor PCBM from severe aggregations under prolonged annealing time. By doping only 5 wt% P3HT–PEO, the device-5 (with 5 wt% P3HT–PEO) exhibited a PCE of 3.60% with thermal annealing at 150 °C for 10 min and remained at 3.61% after annealing for 120 min. In contrasted to the device-0 (without P3HT–PEO), the PCE decreased from 3.26% to 1.61% after annealing at 120 min, which also showed lager clusters of PCBM. This finding will inspire new design of additive materials that can control BHJ morphology through to realize highly efficient and thermally stable solar cells.